Health safety multidisciplinary approach to the study of oral health quality of life - Popović Željka; Gajić Ivanka; Obradović-Đuričić Kosovka; Milošević Dragoslav P. (Војно дело, 2014)
The aim of this paper is to promote the necessity of a multidisciplinary approach to the study of oral health and oral health quality of life. When it comes to oral health, multidisciplinary approach requires the study of oral health from a medical and dental point of view, but also from a social and socio-medical aspects, with full appreciation of the importance of psycho-social problems caused by oral diseases. It is obvious that there is a professional need to define a multidimensional model for monitoring of dental patients, which will enable the provision of relevant indicators for the assessment of oral health problems, and hence for planning and programming of measures in the field of dentistry, from the aspect of public health, and socio-medical standpoint.